Screening of potential bacteria with antagonism properties isolated from pond water in the forest of Universiti Teknologi MARA Negeri Sembilan Kuala Pilah Campus / Azfaizzati Mohd Yakop - Mohd Yakop, Azfaizzati (Faculty of Applied Sciences, 2014)
Pond water in forest of UiTM Negeri Sembilan Kuala Pilah Campus faced algal bloom where abundance of bacteria living in it. The bacteria colonizing that area might be potential bacteria with natural antimicrobial ability. One of the objectives of this study is to obtain pool of bacteria from the pond water. The bacteria isolated been tested on its antagonism ability by cross-streaking technique and well-diffusion technique. This present study is also to identify gram positive bacteria with negative haemolysis activity. The methods involved isolating the bacteria from the pond water and purified the bacteria. The bacteria were then tested using cross-streaking method for their antagonism test followed by haemolysis test and gram staining. Lastly the bacteria were confirmed by another antagonism test using well-diffusion method. From the 81 types of bacteria isolated, only eight types show negative haemolysis with gram positive type, but none of the bacteria have the antagonism ability.